Marcas de colonialidade cultural na formação filosófico-educacional brasileira - Messias, Elvis Rezende (2023)
This work presents the results of a research on the issue of marks of cultural coloniality in Brazilian philosophical-educational training. It aims to understand fundamental elements of the process of construction of the Brazilian philosophical-educational reality, bringing data to light to, consequently, problematize the root and presence of cultural coloniality in this field of our daily work. The questions that move this qualification report lead us to investigate what are the marks of coloniality, especially cultural, present in the process of philosophical-educational formation in Brazil and what original contributions the philosophy of Brazilian education has to offer in this regard. First, a small academic-professional memoir of the author is presented, punctuating the paths taken and until the arrival at the doctorate and challenges faced in the process of writing the report. Subsequently, the main stages and sections of the report are presented, with a view to providing a preview of what is systematized in each of its chapters. Regarding its methodology, this research report is the result of a bibliographical and documental research, with a qualitative approach, of a theoretical nature, with an exploratory procedure and under the primate orientation of the decolonial inflection, in complementary dialogues with the paradigms of interculturality, complexity and the evidentiary paradigm. Regarding the structure of the chapters, at first, the main categories of theoretical analysis to be developed are worked on, with the aim of clarifying the relationships between metropolitan culture and colonized cultures. In a second moment, it starts with the cultural discussion, seeking to explain the complementary relationship between decoloniality and interculturality and the concept of cultural coloniality. The next moment investigates the philosophical-educational matrices that most marked our intellectual formative process, starting, above all, from those most in force in Portugal between the XVI and XIX centuries. The fourth moment, in turn, focuses on the historical-philosophical course of Brazilian education, identifying historical periods, philosophical currents and possible marks of cultural coloniality inherited by us. In the fifth moment, finally, evidence of the main identified marks of cultural coloniality are presented, followed by counterpoints of decolonial resistance (marks of decoloniality) and important tasks that can be assumed as original contributions of the philosophy of Brazilian education.